Analisis komposisi unsur Fe terhadap nilai suseptibilitas magnetik di Kota Padang menggunakan metode X-Ray Fluorescence (XRF) (Analysis of the elemental composition of the magnetic susceptibility value in Padang City using the X-Ray Fluorescence (XRF) method) - Elsa Feryani Harifan; - Mahrizal; Fatni Mufit (Department of Physics – Universitas Negeri Padang UNP, 2015)
Many industrial processes such as steel and cement production produces shaped particles of dust and fly ash. The particles containing pollutants shaped magnetic minerals belonging to the type of iron sulfide minerals iron and titanium sulfide. These pollutants come from the burning of coal. Basically, before burning coal is not magnetic. In the combustion process produces pyrite which decompose and form pyrrhotite and sulfur gases. At temperatures above about 1350 K, pyrrhotite decomposes into iron and sulfur. Iron (Fe) is the most dangerous heavy metals contained in the topsoil. In this study measured the magnetic susceptibility values and elemental composition to analyze the elemental composition Fe of the magnetic susceptibility values,The sample in this study is the topsoil. Measurements of magnetic susceptibility values topsoil samples performed using magnetic susceptibility meter. Then the measurement of the elemental composition of ten samples using X-Ray Fluorescence (XRF) spectrometer. Measurement data plotted in the form of a graph to show the relationship of the value of the elemental composition of Fe magnetic suseptbilitas. Meanwhile, the results of magnetic susceptibility meter, magnetic susceptibility values can inform the type of magnetic minerals based on magnetic susceptibility values.The results of this study indicate that the intensity of the magnetic susceptibility is not only influenced by the composition of the elements Fe, but also influenced by other elements contained in topsoil samples, such as Al, Si, Ca, and Ti. Weight percentage of Fe and Ti derived from the main constituent mineral iron is ilmenite, are paramagn